Functional and molecular characterization of rod-like cells from retinal stem cells derived from the adult ciliary epithelium. - Gian Carlo Demontis; Claudia Aruta; Antonella Comitato; Anna De Marzo; Valeria Marigo (PLoS ONE)
In vitro generation of photoreceptors from stem cells is of great interest for the development of regenerative medicine approaches for patients affected by retinal degeneration and for high throughput drug screens for these diseases. In this study, we show unprecedented high percentages of rod-fated cells from retinal stem cells of the adult ciliary epithelium. Molecular characterization of rod-like cells demonstrates that they lose ciliary epithelial characteristics but acquire photoreceptor features. Rod maturation was evaluated at two levels: gene expression and electrophysiological functionality. Here we present a strong correlation between phototransduction protein expression and functionality of the cells in vitro. We demonstrate that in vitro generated rod-like cells express cGMP-gated channels that are gated by endogenous cGMP. We also identified voltage-gated channels necessary for rod maturation and viability. This level of analysis for the first time provides evidence that adult retinal stem cells can generate highly homogeneous rod-fated cells.